Analysis of the Application of Underpass at the Cibiru Roundabout Using PTV VISSIM - Bangga Fitriyanda Umar; Khalda Khalda; Silvina Sintianti; Shinta Novriani (Riviera Publishing, 2024)
Traffic congestion is a persistent global issue, particularly in densely populated cities like Bandung, Indonesia. The construction of an underpass offers a potential solution to reduce congestion at high-density intersections, such as the Cibiru Roundabout, which connects JL. Soekarno-Hatta, JL. Cibiru, and JL. A.H Nasution. This research analyzes traffic performance and assesses the feasibility of implementing an underpass at this location. A quantitative descriptive research method was used, with data collected through field measurements of vehicle volume and speed. The analysis followed the Indonesian Road Capacity Guidelines (PKJI) 2023 to evaluate capacity, degree of saturation, and service level. Using PTV VISSIM software, simulations were conducted to project traffic conditions over the next ten years, considering a 5% annual growth rate. Results indicate significant congestion, with service levels reaching